Jubilee of Balashova Natalia Nikolaevna - L.K. Gurkina (Овощи России, 2009)
Recognized scientists in the plant protection, immune genetics and gamete selection Natalia Nikolaevna Balashova celebrates her 80th anniversary on this date 18th of June 2009. A corresponding fellow of Academy of Agricultural Science of Moldavia, Academician of International Academy of Informatization Veteran of Labor, professor she worked as a leading researcher of a laboratory of gamete selection and molecular methods; a deputy head of the All-Russian Research Institute of Vegetable Breeding and Seed Production, RAAS from 1992 to 1999; a head of laboratory of gamete selection and molecular methods from 1991 to 2002.